Non-inferior antibody levels for HPV16/18 after extended two-dose schedules compared with a six-month interval: findings of a systematic review and meta-analysis. Issue 10 (3rd October 2021) - Collins-Fairclough, Aneisha; Donken, Robine; Nosyk, Bohdan; Dobson, Simon; Ogilivie, Gina; Sadarangani, Manish
ABSTRACT: Protection after human papillomavirus (HPV) vaccination can be maximized by optimizing vaccination schedules. We systematically reviewed immunogenicity and effectiveness of HPV vaccines administered 6 months apart compared with longer intervals. Seroconversion to vaccine-type HPV was non-inferior for 12- compared with 6-month intervals, but inconclusive for comparison of 36–96 months with 6 months. A 12-month interval showed non-inferior (margin 0.5) vaccine-type HPV antibody responses compared with a 6-month interval. Compared to 6 months, an interval of 36–96 months resulted in non-inferior antibody responses for HPV6 and high-risk types HPV16 and 18, but did not lead to a non-inferior antibody response for HPV11 (GMR 0.63, 95% CI:0.41–0.97). Data on the effectiveness of extended two-dose schedules were limited. Our findings indicate that HPV immunization programs could adopt a 12-month interval instead of 6 months for increased flexibility without compromising immunogenicity. Further evaluation to confirm the immunogenicity and effectiveness of intervals beyond 12 months is warranted.